2014
DOI: 10.1158/1078-0432.ccr-13-2702
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Tumor PD-L1 mRNA Expression Is Associated with Increased TILs and Better Outcome in Breast Carcinomas

Abstract: Purpose: Blockade of the PD-1/PD-L1 axis emerged as a promising new therapeutic option for cancer that has resulted in lasting responses in metastatic renal, lung carcinomas, and melanomas. Tumor PD-L1 protein expression may predict response to drugs targeting this pathway. Measurement of PD-L1 protein is limited by the lack of standardized immunohistochemical methods and variable performance of antibodies. Our goal was to correlate PD-L1 mRNA expression with clinical variables in primary breast carcinomas.Exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

44
367
10
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 448 publications
(430 citation statements)
references
References 41 publications
44
367
10
9
Order By: Relevance
“…Several researches also described similar association. 23,31,32 This correlation was in accordance with the previous finding that IFNg, expressed by activated CD8 C T cells, can induce PD-L1 expression in the surrounding tumor cells. 33 Moreover, seven patients (Table 2) with absent or focal TILs still presented PD-L1 positivity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several researches also described similar association. 23,31,32 This correlation was in accordance with the previous finding that IFNg, expressed by activated CD8 C T cells, can induce PD-L1 expression in the surrounding tumor cells. 33 Moreover, seven patients (Table 2) with absent or focal TILs still presented PD-L1 positivity.…”
Section: Discussionsupporting
confidence: 92%
“…However, the prognostic effect of tumor PD-L1 expression varies across different cancer types and in different studies. [23][24][25] In addition, some studies have demonstrated the correlation of PD-L1 expression in TILs with clinical outcome. 26,27 Recently, a study with 37 penile cancer patients indicated that high level of PD-L1 expression in tumor cells is correlated with LN metastasis and poor CSS.…”
Section: Discussionmentioning
confidence: 99%
“…Many antibodies are available but lack specificity and reproducibility, 40,41 the optimal positivity cut-off is not defined, and staining interpretation suffers from subjectivity. These limitations led to the use of alternative methods, such as mRNA analysis based on in situ hybridization (ISH), 42 DNA microarrays, 43 or quantitative real-time polymerase chain reaction (qRT-PCR). 44 A positive relationship between protein and mRNA expression has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…44 A positive relationship between protein and mRNA expression has been reported. 42 One limitation of DNA microarray-or qRT-PCR-based measurements is that they quantify expression level of both tumor and non-tumor cells present in the sample. This is particularly critical for carcinomas, although results are consistent with those reported using ISH.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PD-L1 is a valuable prognostic marker; the correlation between PD-L1 expression infiltration of tumor by lymphocytes (TILs) [16], high histological grade of tumor [17] and worse clinical outcome [18] is already determined. Nowadays research activities are focused on PD-1/ PD-L1 signaling through the application of humanized monoclonal antibodies (e.g., Nivolumab).…”
Section: Introductionmentioning
confidence: 99%